Novel Neuromodulation Approach to Improve Left Ventricular Contractility in Heart Failure: A First-in-Human Proof-of-Concept Study - Y. Reddy, Vivek; Petrů, Jan; Málek, Filip; Stylos, Lee; Goedeke, Steve; Neužil, Petr (Circulation. Arrhythmia and electrophysiology, 2020)
Morbidity and mortality outcomes for patients admitted for acute decompensated heart failure are poor and have not significantly changed in decades. Current therapies are focused on symptom relief by addressing signs and symptoms of congestion. The objective of this study was to test a novel neuromodulation therapy of stimulation of epicardial cardiac nerves passing along the posterior surface of the right pulmonary artery. Fifteen subjects admitted for defibrillator implantation and ejection fraction ≤35% on standard heart failure medications were enrolled. Through femoral arterial access, high fidelity pressure catheters were placed in the left ventricle and aortic root. After electro anatomic rendering of the pulmonary artery and branches, either a circular or basket electrophysiology catheter was placed in the right pulmonary artery to allow electrical intravascular stimulation at 20 Hz, 4 ms pulse width, and ≤20 mA. Changes in maximum positive dP/dt (dP/dt ) indicated changes in ventricular contractility. Of 15 enrolled subjects, 5 were not studied due to equipment failure or abnormal pulmonary arterial anatomy. In the remaining subjects, dP/dt increased significantly by 22.6%. There was also a significant increase in maximum negative dP/dt (dP/dt ), mean arterial pressure, systolic pressure, diastolic pressure, and left ventricular systolic pressure. There was no significant change in heart rate or left ventricular diastolic pressure. In this first-in-human study, we demonstrated that in humans with stable heart failure, left ventricular contractility could be accentuated without an increase in heart rate or left ventricular filling pressures. This benign increase in contractility may benefit patients admitted for acute decompensated heart failure.